Treasure trove of benefits and variety at the table : a fourteenth-century Egyptian cookbook - Nasrallah, Nawal. (Islamic History and Civilization, 2018)
The Kanz al-fawāʾid fī tanwīʿ al-mawāʾid , a fourteenth-century cookbook, is unique for its variety and comprehensive coverage of contemporary Egyptian cuisine. It includes, in addition to instructions for the cook, a treasure trove of 830 recipes of dishes, digestives, refreshing beverages, and more. It is the only surviving cookbook from a period when Cairo was a flourishing metropolis and a cultural haven for people of diverse ethnicities and nationalities. Now available for the first time in English, it has been meticulously translated and supplemented with a comprehensive introduction, glossary, and 117 color illustrations to initiate readers into the world of the Kanz al-fawāʾid . The twenty-two modern adaptations of Kanz recipes will inspire further experimentations. It is a valuable resource for scholars of medieval material culture, and for all lovers of good food and cookbooks.